Total Knee Arthroplasty in Octogenarians: Should We Still Be so Restrictive? - Trigueros-Larrea, Jose Maria (Geriatrics (Basel), 2021)
Demand for total knee arthroplasty (TKA) in octogenarians will increase in subsequent years as society ages. We conducted a retrospective observational study in octogenarians operated on with TKA between 2015 and 2019, comparing preoperative and postoperative Knee Society Score (KSS), Knee Society Function Score (KSFS), extension and flexion balance, and radiologic alignment using a paired Student t-test. A chi-squared test was used to correlate mortality with Charlson comorbidities index score and with ASA scale. Kaplan–Meier analysis was performed to calculate patient survival. In this period 36 patients ≥80 years underwent TKA, with a mean age of 81.6 years. Of these, 24 patients (66.7%) were classified as ASA II and 12 (33.3%) as ASA III. Sixteen patients (44.4%) were Charlson 0, 14 (38.9%) Charlson 1, two (5.6%) Charlson 2, and four (11.1%) Charlson 3. KSS, KSFS, flexion and extension range, and radiologic alignment were statistically significant (p < 0.001) when comparing preoperatory and post-operatory data. No correlation (p > 0.05) was found between mortality and ASA or Charlson score. Seven patients (19.4%) suffered a medical complication and two patients experienced surgical complications. Four patient died (11.1%) during follow-up. The mean patient survival was 67.4 months. Patients ≥80 years achieve clinical improvement after TKA. Comorbidities, not age, are the burden for surgery in older patients.